Green power leaf & flower vegetables - Hughes, Meredith Sayles (Hughes, Meredith Sayles. Plants we eat., 2001)
Describes the history, growing requirements, uses, and food value of various leafy green vegetables and vegetable flowers, including cabbage, broccoli, artichokes, spinach, Belgian endive, and lettuce. Includes recipes.